Anatomical mapping and quantitative functional analysis of lower limb lymphatic flow in normal cynomolgus monkeys using indocyanine green lymphography - Jihun Kim; Gyu-Seo Bae; Yujin Kim; Jiyoung Yang; Eunsu Jeon; Jincheol Seo; Youngjeon Lee; Sungin Lee (PLoS ONE, 2025)
Background The lymphatic system is essential for fluid balance and immune regulation, but its anatomy and function in translational models remain insufficiently defined. Indocyanine green (ICG) near-infrared fluorescence lymphography enables real-time visualization of superficial lymphatics, yet baseline functional data in non-human primates are lacking. Cynomolgus monkeys closely resemble humans and represent a relevant model for lymphatic research. This study established baseline drainage patterns and functional contractility metrics of the lower limb lymphatic system. Methods Five healthy female cynomolgus monkeys were studied, with a total of 10 lower limbs evaluated. Lymphatic drainage was mapped using 11 intradermal injection sites and near-infrared fluorescence imaging. For functional analysis, ICG was injected into the anteromedial and anterolateral regions, which consistently exhibited clear lymphatic channels suitable for signal extraction. Fluorescence signals were analyzed using peak–valley and wavelet methods to quantify contraction metrics. Functional parameters were assessed at multiple time points for temporal stability. Comparisons were performed within each pathway, and pooled values were used for paired comparisons between the medial and lateral pathways. Results Anatomical mapping revealed four major drainage groups. The anteromedial, posteromedial, and anterolateral regions drained predominantly to the inguinal lymph node, whereas posterolateral regions drained mainly to the popliteal lymph node. Functionally, lymphatic contractions remained temporally stable, and medial pathways exhibited significantly higher peak frequency, wavelet mean frequency, amplitude, and wavelet amplitude compared with that of the lateral pathways, indicating more frequent and stronger contractions. Lateral pathways showed slightly greater variability in contraction rhythm. Conclusion This study provides the first integrated anatomical and functional characterization of lower limb lymphatics in cynomolgus monkeys. The findings establish baseline parameters that may guide comparative analyses, support pathway-specific investigations, and serve as baseline data for future studies of lymphatic dysfunction and disease modeling in non-human primates.